Diagnosis of a case of relapse of acute lymphoblastic leukemia based on oral manifestation of leukemic gingival enlargement and acute necrotizing gingivitis: A case report - Gopikrishna Kolli; Nagaraja Chaitra; Vikash Ranjan; Dilip Kumar Nateshkumar (Wolters Kluwer Medknow Publications, 2014)
Acute leukemias are the most common malignancy in childhood. They represent approximately 30% of malignant diseases in patients under the age of 15 years. Acute lymphoblastic leukemia (ALL) is the most frequent type of leukemia in children. Despite high cure rates, approximately 20% of patients with ALL have disease relapse. Oral manifestations are common in leukemia, particularly in acute leukemias. One of the oral manifestations of leukemia is diffuse gingival enlargement thought to be, at least partly, the result of gross infiltration of the gingiva by blast cells. The occurrence of acute necrotizing gingivitis, although a rare occurrence, is seen in such immunocompromised individuals. This is a case report of a 19-year-old patient who was under remission after treatment for ALL in whom a recurrence of leukemia was detected based on the oral findings and highlights the importance of its early detection by the dentist in preventing further complications and for instituting therapy swiftly.